Determination of antitumor properties of synthesized chalcone-phosphazenes containing dioxybiphenyl groups against PC-3 and LNCaP cell lines - Tekin, S.; Koran, K.; Ozen, F.; Sandal, S.; Gorgulu, A. O. (Wiley-Blackwell, 2014)
[Abstract Not Available]
Keywords: Phosphazene; Chalcone; PC-3; LNCaP; cell viability; MTT assay